2018
DOI: 10.1111/jdv.15107
|View full text |Cite
|
Sign up to set email alerts
|

Prurigo nodularis: a physician survey to evaluate current perceptions of its classification, clinical experience and unmet need

Abstract: EADV Task Force Pruritus notes several challenges that must be met to improve symptoms and quality of life for patients with PN.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
33
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(38 citation statements)
references
References 27 publications
2
33
0
3
Order By: Relevance
“…Despite PN’s fairly frequent occurrence in the clinical setting, studies on the prevalence and incidence of PN have to date consisted of small case studies and case reports. To ascertain the incidence of PN, Pereira et al performed a survey study across 14 countries and demonstrated that 60% of respondents, on average, saw fewer than five PN patients per month presenting to clinic 16. Overall, epidemiological studies are lacking.…”
Section: Epidemiologymentioning
confidence: 99%
“…Despite PN’s fairly frequent occurrence in the clinical setting, studies on the prevalence and incidence of PN have to date consisted of small case studies and case reports. To ascertain the incidence of PN, Pereira et al performed a survey study across 14 countries and demonstrated that 60% of respondents, on average, saw fewer than five PN patients per month presenting to clinic 16. Overall, epidemiological studies are lacking.…”
Section: Epidemiologymentioning
confidence: 99%
“…Although occurring for a prolonged period of time owing to the long‐lasting itch, scratching behaviour is usually not compulsive or obsessive. These compulsive or obsessive behaviours may, however, develop in the course of the chronic prurigo condition, even occurring when no itch is perceived . Patients presenting with SISL do not report itch, and thus, the skin lesions result from pathological manipulation due to psychological aetiology rather than as an alleviating response to intense itch .…”
Section: Delimitation To Self‐inflicted Skin Lesionsmentioning
confidence: 99%
“…Establishing a clear definition and classification of chronic prurigo was an important first step to ultimately achieve a better care. Recently, specialists in the field of chronic pruritus identified unmet needs, namely a more comprehensive understanding of the pathophysiology underlying chronic prurigo and novel more effective therapies …”
Section: Unmet Needs and Future Perspectivesmentioning
confidence: 99%
See 1 more Smart Citation
“…However, we report more frequent topical therapy and less frequent systemic therapy prescriptions. 5 As PN continues to be studied, more evidence-based treatment options will emerge to provide additional guidance for healthcare providers. Since multiple healthcare providers manage PN, it is important to consolidate treatment recommendations to prevent mismanagement.…”
mentioning
confidence: 99%